Miss Marple e a figuração da mulher no romance policial inglês - Moraes, Adelle Paiva Proença de (2021)
Agatha Christie is, still in contemporary times, one of the biggest names in the 20th century detective novel, with works consumed around the world for more than a century, highlighting its relevance in the literature of the genre. This dissertation aims to interpret the tenth detective novel published by the author, Murder at the Vicarage (1930) [Assassinato na Casa do Pastor, 2013]. To this end, we chose to read from the perspective of dialectical criticism, which promotes a dialogue between literature and society. The reading will be guided by the three interpretative levels proposed by Fredric Jameson, in order to articulate the form – or the manifest content of the work – to the social issues raised in the plot, such as the urgency of a female role in the 20th century English patriarchal society. For this purpose, the choice for a novel that introduces a female character as a detective elucidates the issues of women's protagonism in the social sphere and figured in the work in question.